An updated and annotated checklist of recent nonmarine ostracods from China - Yu, Na; Zhao, Quanhong; Li, Erchao; Chen, Shimei; Chen, Liqiao (Zootaxa, 2009)
The updated and annotated checklist includes all published names of Chinese recent nonmarine ostracods and their provincial records up to 2007. A total of 160 specific names are included. Of these, 154 are taxonomically accepted names. At present, the richest province with more than 53 species of ostracods is Qinghai, followed by Yunnan with 42 species and Tibet with 30 species. There are still fourteen provinces in China without records, and two provinces with only one ostracod reported. These provinces are in need of immediate investigation.